Distribuição anual de partos em caprinos no sudoeste Província de Chaco, Argentina - SMERIGLIO, Aldo R. (Universidad Nacional del Litoral, 2020)
The distribution of births in goats during the year determines the volume of commercial offer along that year. However, this could be condicionated by the management system used. Therefore the objective of this work was to evaluate the distribution of births in herds of goats in the southwest of the province of Chaco, Argentina. The study was carried out by surveying 541 births in 6 establishments under 2 types of management: extensive (n= 447) and semi-intensive (n= 93). The data were taken in spreadsheets by each goat producer. An exploratory and descriptive analysis was carried out using the Infostat statistical software. It was observed that the highest concentration of births occurred mainly in the months of winter and autumn in the extensive systems, however differences were found with the semi-intensive system, where the occurrence of births was homogeneous throughout the year with a slight increase in the spring months. In conclusion, the distribution of births is affected by the type of production system used, achieving a uniform commercial offer throughout the year with the intensification of the system.